Genotyping of Plasmodium vivax by minisatellite marker and its application in differentiating relapse and new infection. (December 2016) - Das, Ram; Dhiman, Ramesh; Savargaonkar, Deepali; Anvikar, Anupkumar; Valecha, Neena
Abstract Background Plasmodium vivax malaria is a major public health problem in India. Control of vivax malaria is challenging due to various factors including relapse which increase the burden significantly. There is no well studied marker to differentiate relapse from reinfection. This creates hindrance in search for anti-relapse medicines. The genomic study of minisatellite can help in characterization of relapse and new infection of vivax malaria. Methods Eighty-eight samples ofP. vivax were collected from malaria clinic. All the 14 chromosomes ofP. vivax were scanned for minisatellite marker by Tandem Repeat Finder software Version 4.07b. Minisatellite marker CH1T1M13779 from chromosome one was applied for genotyping in 88 samples ofP. vivax including 2 recurrence cases. Results Whole genome ofP. vivax was scanned and found to have one hundred minisatellite markers. CH1T1M13779 minisatellite marker from chromosome-1 was used for amplification in 88 samples ofP. vivax. Of 66 amplified samples, 14 alleles were found with varied allele frequency. The base size of 280 (13.63 %) 320 bp (13.63 %) and 300 bp (16.66 %) showed the predominant allele in theP. vivax population. Genotyping of two paired samples (day 0 and day relapse) could demonstrate the presence of relapse and reinfection. Conclusion The CH1T1M13779 can be potential minisatellite marker which can be used to differentiate between relapse and new infection ofP. vivax strain.